2017
DOI: 10.7860/jcdr/2017/29063.10201
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Ductal Carcinoma Breast: How Neoadjuvant Chemotherapy Affects the Status of Estrogen Receptor, Progesterone Receptor and HER2/Neu- A Tertiary Care Centre Study

Abstract: Accurate determination of ER, PR and Her2/neu status in primary IDC breast is important to guide further treatment. Change in receptor status post NAC may warrant corresponding change in hormonal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This study showed no significant change of HER-2 expression before and after neoadjuvant chemotherapy which in accordance [29]. However others reported significant change of HER2 (7.1%) (25), 24-21% (26), and 4.7% [27].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study showed no significant change of HER-2 expression before and after neoadjuvant chemotherapy which in accordance [29]. However others reported significant change of HER2 (7.1%) (25), 24-21% (26), and 4.7% [27].…”
Section: Discussionsupporting
confidence: 84%
“…Some authors noticed significant loss of progesterone receptor positivity only after neoadjuvant chemotherapy and estrogen receptor did not show any significant change [29,30].…”
Section: Discussionmentioning
confidence: 99%